The utilization of rice hull ash in hot mix asphalt - Chan, Mark Brandon Y.; Dela Rama, Raymond Joseph C.; Caram, Rosabelle Louise A. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
This study aimed to utilize and determine the effects of rice hull ash (RHA), as partial fine aggregate replacement, on the properties of hot mix asphalt (HMA). The mix designs for the control and asphalt concrete with RHA replacements, known as modified asphalt concrete, were made based on the DPWH Blue Book. Three different tests, namely: Marshall stability and flow test, theoretical maximum specific gravity test, and immersion-compression test, were conducted. The volumetric (i.e. percent air voids, percent voids filled with asphalt, percent voids in mineral aggregates) and performance properties (i.e. stability, flow, compression strength, index of retained strength) of the samples were obtained from the tests to verify if the samples complied with the requirements for surface course HMA concrete that can withstand heavy traffic loads. Analysis of the results showed that 5% RHA replacement is the optimal replacement of fine aggregates in asphalt concrete. 5% RHA replacement gave the highest flow value that passed the requirements. It has increased Marshall stability and flow values compared to the control. Furthermore, it has higher dry and wet compressive strength values compared to the control. Though 5% might appear to be a small amount considering the tons of rice hull waste produced every year, it would still be beneficial, as this would decrease the waste material to be dumped in landfills.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Rice hull ash; Asphalt